A compact and simpler formulation of the component method for steel connections. (January 2020) - Gil-Martín, L.M.; Hernández-Montes, E.
Abstract: A simpler and a more general formulation of the component method (CM) proposed by the European Standard of Steel Structures is presented in this work. There are two main differences from the methodology proposed in Eurocode 3-Part 1–8: first) the moment-rotation curve is obtained from the moment and axial equilibrium equations using only the translational stiffness (springs) of the components (i.e. avoiding the concept of rotational stiffness), and two) the shear response of the column panel zone is distributed over the joint and located at the level where other components exist, instead of concentrating it at the level of the compression zone, as Eurocode 3-Part 8 does. By using basic kinematic conditions and solving a simple system of equations, all the information regarding the behavior of the joint is obtained. Two examples are presented. Highlights: A new approach of the component method (CM) for steel connections is presented. Each focus of deformation is modeled as a translational spring. Complete curves Moment-rotation are obtained. Strength and initial stiffness results coincide with Eurocode 3 methods.